2011
DOI: 10.1002/nau.21149
|View full text |Cite
|
Sign up to set email alerts
|

Can hypopressive exercises provide additional benefits to pelvic floor muscle training in women with pelvic organ prolapse?

Abstract: Adding hypopressive exercises to PFMT does not improve PFM function. Both treatment groups performed better than the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 18 publications
4
60
0
6
Order By: Relevance
“…Resende et al 13 reported results from a single‐blinded clinical trial where 58 women diagnosed of mild pelvic organ prolapse received a physical therapy treatment based on PFM exercises alone or combined with HEs. The PFM exercises significantly increased PFM strength, endurance, neuromuscular activation, 13 and thickness 14 regardless of whether or not women also performed HEs. Despite these results, HEs are currently being advocated by many clinicians for the treatment of pelvic floor dysfunctions in women.…”
Section: Discussionmentioning
confidence: 99%
“…Resende et al 13 reported results from a single‐blinded clinical trial where 58 women diagnosed of mild pelvic organ prolapse received a physical therapy treatment based on PFM exercises alone or combined with HEs. The PFM exercises significantly increased PFM strength, endurance, neuromuscular activation, 13 and thickness 14 regardless of whether or not women also performed HEs. Despite these results, HEs are currently being advocated by many clinicians for the treatment of pelvic floor dysfunctions in women.…”
Section: Discussionmentioning
confidence: 99%
“…Few runners practiced exercises to strengthen their pelvic floor, but still showed good electrical activity in the maximal voluntary contraction. In a study of Resende et al [14], which examined 28 nulliparous volunteers, found MVC 99.8 mV, a result very similar to that of runners from more than 25 km (91.08 mV). In our sample of runners, no significant differences were observed between the groups in relation to pubovisceral muscle injuries or its thickness.…”
Section: Discussionmentioning
confidence: 71%
“…SEMG has been used to evaluate pelvic muscle activation patterns in women with urinary incontinence and genital prolapse, both in maximum voluntary contraction (MVC) and in Valsalva [13,14]. However, there are no studies in the literature comparing 3DUS and SEMG for pelvic floor evaluations on female runners.…”
Section: Introductionmentioning
confidence: 99%
“…The first did not find any acute effect of adding AHT to PFMT on PFM maximal voluntary contraction, endurance and muscle activation 8. The RCT followed 58 women with stage II POP in a 12 weeks’ intervention of adding AHT to PFMT.…”
Section: What Is the Aht And How Should It Work?mentioning
confidence: 98%
“…Let’s consider the two studies on the effect of the AHT for pelvic floor dysfunction: one experimental study8 and one RCT 9. The first did not find any acute effect of adding AHT to PFMT on PFM maximal voluntary contraction, endurance and muscle activation 8.…”
Section: What Is the Aht And How Should It Work?mentioning
confidence: 99%